Eptifibatide-induced profound thrombocytopaenia: a rare complication - Mahajan, Pranav (BMJ Case Rep, 2021)
Drug-induced immune thrombocytopaenia (DITP) is a type of thrombocytopaenia caused by medications. It is one of the common causes of unexplained thrombocytopaenia. It is caused by the formation of autoantibodies against a particular drug and is commonly observed with medications like heparin and beta-lactam antibiotics. One of the rare causes of DITP is eptifibatide, a widely used antiplatelet agent for pretreatment in cardiac catheterisation. These patients can be asymptomatic or develop complications like skin bruising, epistaxis and even intracranial haemorrhage. We present a case of a 64-year-old man who developed eptifibatide-induced profound thrombocytopaenia leading to extensive skin bruising. He was treated with platelet transfusions followed by prompt improvement in platelet count.